2018
DOI: 10.1029/2018gc007882
|View full text |Cite
|
Sign up to set email alerts
|

Late Cenozoic Erosion Estimates for the Northern Barents Sea: Quantifying Glacial Sediment Input to the Arctic Ocean

Abstract: A compilation of seismic data has been used to characterize the Neogene‐Quaternary sedimentary succession of the northwestern Barents Sea continental margin to better understand the paleoenvironmental evolution and the sedimentary processes involved. The Neogene strata are dominated by contourites related to the ocean circulation established from the opening of the Fram Strait connecting the Atlantic and the Arctic Oceans (< ~17.5 Ma). The upper Plio‐Pleistocene strata (< ~2.7 Ma) are dominated by stacked grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 129 publications
2
13
0
Order By: Relevance
“…2B), which suggest an extensive ice sheet in this region. This supports the earlier conclusions of Knies et al (2009) and Lasabuda et al (2018), who, based on IRD records and identification of GDFs, suggested an ice sheet with active ice streams covering Svalbard and the adjacent continental margins. Identification of glacial-derived sediments in shelf-edge wells (Knies et al, 2009) and the development of a well-defined upper-slope depocenter (Fiedler and Faleide, 1996) at the southwestern Barents Sea margin support the supposition that NHG phase I sedimentation rates (Fig.…”
Section: Euris Reconstructionsupporting
confidence: 91%
See 1 more Smart Citation
“…2B), which suggest an extensive ice sheet in this region. This supports the earlier conclusions of Knies et al (2009) and Lasabuda et al (2018), who, based on IRD records and identification of GDFs, suggested an ice sheet with active ice streams covering Svalbard and the adjacent continental margins. Identification of glacial-derived sediments in shelf-edge wells (Knies et al, 2009) and the development of a well-defined upper-slope depocenter (Fiedler and Faleide, 1996) at the southwestern Barents Sea margin support the supposition that NHG phase I sedimentation rates (Fig.…”
Section: Euris Reconstructionsupporting
confidence: 91%
“…2B) could suggest that the KBSIS did not extend to the shelf edge. However, identification of GDFs (Laberg et al, 2010;Lasabuda et al, 2018) implies that the KBSIS was located at the shelf edge and that ice streams were active also in NHG phase III. Fiedler and Faleide (1996) and Hjelstuen et al (1996) showed that the character of bedrock exposed to erosion in the catchment areas of the Bjørnøya and Storfjorden TMFs (Fig.…”
Section: Euris Reconstructionmentioning
confidence: 99%
“…These first-order estimates allow us to compare different sediment sources and their relative influences on ocean basin sedimentation. The calculated sedimentation rates for this ocean current system are one order of magnitude lower than the average rates calculated for the subsequent deposits from the Quaternary Barents Sea Ice Sheet (Laberg et al, 2012) in the same area and on the Northern Barents Sea margin ( Figure 9) (Lasabuda et al, 2018a). These numbers therefore support the finding of Lasabuda et al (2018b), that is, that there was a pronounced increase in sedimentation rate on the SW Barents Sea continental margin following the establishment of Northern Hemisphere Glaciations in the Quaternary.…”
Section: Average Sedimentation Rate For the Bjørnøyrenna Driftsupporting
confidence: 66%
“…MTDs make up a significant component of the upper‐slope stratigraphy, suggesting that sediment slides and slumps contributed to the basinwards transfer of sediment in our study area (Figures 5b–d, 6a–d, and 7a). We do not discern any clear patterns in the magnitude or frequency of these events through the Pliocene–Pleistocene, which might have been expected given the inferred increased rate of sediment delivery to this margin from the Early to Middle Pleistocene (Faleide et al., 1996; Laberg & Andreassen, 2007; Laberg et al., 2010) and the accompanying changes in ocean circulation that could influence slope instability (Eiken & Hinz, 1993; Elger et al., 2017; Lasabuda et al., 2018; Osti et al., 2019). Furthermore, between H5 (~1.5 Ma) and H1 (~0.2 Ma), the outer‐shelf in the southern Barents Sea experienced net accumulation and shelf aggradation that may be related to differential subsidence in the shelf and outer shelf area (Faleide et al., 1993b, 1996, 2008), with sediment accumulation within each unit varying from 10 to 700 m in thickness (Figure 3a–e).…”
Section: Discussionmentioning
confidence: 98%